Sunrise through a dust storm - Lev Grigorevich Brodaty:::Creator::::::::::::
Glava Nervaya' (Chapter 1). Sunrise through a dust storm. Pen and ink lithograph. Lev Grigorevich Brodaty was born in Warsaw in 1889. A graphic artist, poster artist and illustrator, he created these for a Russian translation (possibly the first) of The Grapes of Wrath. He died in Moscow in 1954.